THE ESSENTIAL ROLE OF CONCEPTUAL AND THEORETICAL MODELS IN BUSINESS AND FINANCE RESEARCH - Oluwadamilola , Emeka Chinedu (Ayden International Journal of Applied Economics, Finance and Accounting, 2024)
This study employed a comprehensive literature review to identify existing articles that address theoretical and conceptual frameworks. Articles were sourced from reputable academic databases such as Google Scholar, Academia.edu, ResearchGate, among others. This approach involves summarizing and synthesizing existing literature in a narrative format. The study provides a descriptive overview of key concepts, findings, and debates within theoretical and conceptual frameworks as a vital part of business and finance research. The research paper provides a broad overview of a topic or to explore emerging trends and debates. The research was guided by keywords related to theoretical and conceptual frameworks. This study extensively discusses the significance of incorporating theoretical and conceptual frameworks in research, providing thorough justifications for their indispensable role in enhancing research quality. Furthermore, it elaborates on the meanings of these frameworks, their distinct roles in the research process, differences between them and methods of construction. It is imperative for researchers and students to strategically integrate theoretical and/or conceptual frameworks into their research inquiries to enhance robustness across all aspects.